Sustainable futures in the built environment to 2050 a foresight approach to construction and development - Dixon, Timothy J. 1958-; Connaughton, John E.; Green, Stuart 1958- (Hoboken Wiley-Blackwell, 2018)
"Brings together leading thinking on issues of new professional practice and on the future of a sustainable built environment. This book focuses on both construction and development issues, and examines how we can transition to a sustainable future by the year 2050-bringing together leading research and practice at building, neighbourhood, and city levels. It deftly analyses how emerging socio-economic, technological, and environmental trends will influence the built environment of the future. The book covers a broad spectrum of interests across the scales of buildings, communities and cities, including how professional practice will need to adapt to these trends. The broader context is provided by an analysis of emergent business models and the changing requirements for expert advice from clients. Sustainable Futures in the Built Environment to 2050: A Foresight Approach to Construction and Development features chapters covering: data and trends, including historical data and UK and international case studies; policies and practice related to the field; current state of scientific understanding; key challenges; key technological advances (including disruptive and systemic technological innovations); change issues and critical uncertainties; and future visions. It provides: A strong conceptual framework based on a 'Foresight' approach Discussion of the key data and trends that underpin each chapter Coverage of both construction and property development. Specially commissioned chapters by academics and practitioners. A synthesis of the main findings in the book and key insights for the future to 2050 Sustainable Futures in the Built Environment to 2050: A Foresight Approach to Construction and Development is an important book for postgraduate students and researchers, construction, real estate and property development specialists, engineers, planners, architects, foresight and futures studies specialists, and anyone involved in sustainable buildings" -- Provided by publisher.
"This book provides an insight on both construction and development issues and examine how we can transition to a sustainable future by 2050 bringing together leading research and practice at building, neighbourhood and city levels"-- Provided by publisher.
Machine generated contents note: List of Contributors -- Notes on Contributors -- Foreword -- Preface -- Acknowledgements -- Book Endorsements -- 1 Introduction: Foresight and Futures Studies in Construction and Development 1 Tim Dixon, John Connaughton and Stuart Green Part 1 Sustainability and the Built Environment 25 2 Climate Change, Resilience and the Built Environment 27 Janet F. Barlow, Li Shao and Stefan T. Smith 3 Sustainability in Real Estate Markets 50 Jorn van de Wetering 4 From the 'Sustainable Community' to Prosperous People and Places: Inclusive Change in the Built Environment 72 Saffron Woodcraft and Constance Smith 5 Smart and Sustainable?: The Future of 'Future Cities' 94 Tim Dixon 6 Sustainable Infrastructure 117 Martino Tran, Jim Hall, Robert Nicholls, Adrian Hickford, Modassar Chaudry and Geoff Watson 7 Sustainable Design of the Built Environment 137 Lorraine Farrelly Part 2 Changing Professional Practice 155 8 Planning for Sustainability: Reflections on a Necessary Activity 157 Joe Doak and Gavin Parker 9 Sustainable Construction: Contested Knowledge and the Decline of Professionalism 172 Stuart Green 10 Sustainable Procurement 194 John Connaughton and Will Hughes 11 Social Media in the Built Environment 223 Bob Thompson Part 3 Provocations about the Future: Practitioners' Viewpoints 249 12 Sustainability through Collaboration and Skills Development 251 Andy Ford and Aaron Gillich 13 Built Environment Professionals as Sustainability Advocates 270 Gerard Healey Part 4 Transformative Technologies and Innovation 285 14 Energy Interactions: The Growing Interplay between Buildings and Energy Networks 287 Phil Coker and Jacopo Torriti 15 Sustained Innovation Uptake in Construction 310 Graeme D. Larsen 16 Humanising the Digital: A Cautionary View of the Future 325 Ian J. Ewart Part 5 Conclusions and Common Themes 337 17 Understanding and Shaping Sustainable Futures in the Built Environment to 2050 339 Tim Dixon, John Connaughton and Stuart Green Index.
Includes bibliographical references and index.
Keywords: Sustainable development; Construction industry -- Management